2022
DOI: 10.1002/jsfa.12321
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microbial communities and key odourants in fermented capsicum inoculated with Pediococcus pentosaceus and Cyberlindnera rhodanensis

Abstract: BACKGROUND Fermented capsicum (i.e. pickled pepper) is one of the most popular fermented vegetables. However, the effect of inoculated microbial fermentation on pickled pepper is not yet fully understood. RESULTS Cyberlindnera rhodanensis J52 with a rich ester flavour and Pediococcus pentosaceus AL with a strong inhibitory effect on foodborne pathogenic bacteria were selected to prepare single‐ and double‐strain fermented capsicum under low salt (< 10 g L−1 sodium chloride) conditions. The inhibition zone of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The rOAV was employed to assess the contribution of each volatile compound to the overall aroma distribution. Several studies in fermented foods have demonstrated that volatile compounds contribute to specific characteristics of food flavor and can be considered key volatile compounds if the concentration of volatiles is above their odor perception threshold (rOAV ≥1) (Su et al., 2022; Shi et al., 2023; Li et al., 2022). Twenty‐five volatiles distributed in the six previously described categories had rOAVs ≥1 in at least one sample.…”
Section: Resultsmentioning
confidence: 99%
“…The rOAV was employed to assess the contribution of each volatile compound to the overall aroma distribution. Several studies in fermented foods have demonstrated that volatile compounds contribute to specific characteristics of food flavor and can be considered key volatile compounds if the concentration of volatiles is above their odor perception threshold (rOAV ≥1) (Su et al., 2022; Shi et al., 2023; Li et al., 2022). Twenty‐five volatiles distributed in the six previously described categories had rOAVs ≥1 in at least one sample.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the production of lactic acid, butyric acid, and other substances by microorganisms (such as LAB) in the G group during the early fermentation process. As the fermentation time is prolonged, these acidic substances could combine with other substances to form esters and other flavor compounds ( Shi et al, 2023 ). Similarly, the bitterness of pickled peppers in the G group was lower than that in the D group during the whole fermentation stage.…”
Section: Resultsmentioning
confidence: 99%
“…The multisequence phylogenetic analysis confirmed the taxonomic affiliation of the RODW isolates with the Cyberlindnera genus and their closer affiliation with the Cyberlindnera rhodanensis species. The genus Cyberlindnera was introduced as a replacement name for the genus Lindnera and currently accommodates over thirty species, some of which are associated with the fermentation of plant biomass and wastes, as well as phenolic-rich beverages and food products [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In the present study, the fermentation of RODW by the tested indigenous yeast isolates resulted in the fermentation of around 80% of the reducing sugars present in the RODW and a decrease in the phenolic content to around 60% of the initial concentration in the RODW.…”
Section: Discussionmentioning
confidence: 99%